2020
DOI: 10.1097/md.0000000000019244
|View full text |Cite
|
Sign up to set email alerts
|

A novel EDA1 missense mutation in X-linked hypohidrotic ectodermal dysplasia

Abstract: A mutation in the epithelial morphogen gene ectodysplasin-A1 (EDA1) is responsible for the disorder X-linked hypohidrotic ectodermal dysplasia (XLHED), the most common form of ectodermal dysplasia. XLHED is characterized by impaired development of hair, eccrine sweat glands, and teeth. This study aimed to identify potentially pathogenic mutations in four Chinese XLHED families. Genomic DNA was extracted from the peripheral blood and sequenced. Sanger sequencing was used to carry out mutational anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…EDA is a type II membrane protein that can be cleaved by furin to produce a secreted form (10)(11)(12), which is subsequently recognized by the ectodysplasin A receptor (10,(13)(14)(15). EDA acts as a homotrimer and plays an important role in the development of ectodermal tissues such as skin (16,17). EDA, along with c-Met, has also been shown to be involved in the differentiation of anatomical placodes, precursors of scales, feathers and hair follicles in vertebrates (18).…”
Section: Introductionmentioning
confidence: 99%
“…EDA is a type II membrane protein that can be cleaved by furin to produce a secreted form (10)(11)(12), which is subsequently recognized by the ectodysplasin A receptor (10,(13)(14)(15). EDA acts as a homotrimer and plays an important role in the development of ectodermal tissues such as skin (16,17). EDA, along with c-Met, has also been shown to be involved in the differentiation of anatomical placodes, precursors of scales, feathers and hair follicles in vertebrates (18).…”
Section: Introductionmentioning
confidence: 99%
“… 5 Together, these genes are responsible for EDA production, a critical signalling protein in embryogenesis that discerns the ectoderm and mesoderm. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 The ectoderm–mesoderm interactions form the basis for development of skin, hair, nails, teeth and sweat glands. While HIED comprises several distinct features, pulmonary complications are frequent.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic inheritance of HIEDs depends on the underlying genetic anomaly with X‐linked inheritance associated with the ectodysplasin A (EDA, locus Xq12‐q13.1, encoding ligand EDA‐A1) gene and autosomal inheritance with EDA receptor (EDAR) and EDAR‐associated death domain protein (EDARADD) 5 . Together, these genes are responsible for EDA production, a critical signalling protein in embryogenesis that discerns the ectoderm and mesoderm 6–13 . The ectoderm–mesoderm interactions form the basis for development of skin, hair, nails, teeth and sweat glands.…”
Section: Discussionmentioning
confidence: 99%
“…The condition will be delineated into two forms mainly, known as (HED) hypohidrotic or anhydrotic (Christ-Siemens-Touraine syndrome) where endocrine glands are absent or markedly diminished and hydrotic (Clouston syndrome) with normal endocrine glands. The two types show similarities in the involvement of teeth and hair, although the nails and sweat glands show a different pattern [2,15,16] . HED is the most frequent of all dysplasias and brings with it hypodontia, hypohidrosis and hypotrichosis and presents an infant mortality rate between 2 and 20%, all this is going to depend on the precocity of diagnosis and treatment protocols [4, 11-13, 17, 18] .…”
Section: Etiologymentioning
confidence: 99%
“…This gene tends to encode ectodysplasin, which is usually a molecule involved in epithelial-mesenchymal communication during the skin development process. Other genes that can be associated with this dysplasia are the EDAR, EDARADD and WNT10A genes, where it will present a recessive or dominant inheritance pattern [16,[27][28][29] . Studies have shown that the hypohidrotic subtype is X-linked.…”
Section: Geneticsmentioning
confidence: 99%